DEVELOPING ENGLISH LISTENING MATERIALS FOR THE TENTH GRADE STUDENTS OF MUSIC PERFORMING ART VOCATIONAL SCHOOL - Boy Atlaliust Simangunsong; Sumarsih Sumarsih; Rita Suswati (Universitas Negeri Medan, 2017)
The aim of this study was to find out an appropriate English listening materials for the Grade X students of music performing art vocational school. Sekolah Menengah Kejuruan (SMK) or Vocational School is an institution where students are prepared to be work-ready after finishing their education in specific major. Music Performing Art is one of the major provided in Indonesia’s vocational school. By the fact that listening activities are often ignored by teachers and that listening is one of the test in the National Examination, then listening activities are considered important in English learning activity. However, the finding of materials that provided for the Grade X students of Music Performing Art major at SMK Negeri 11 Medan shows that the listening materials provided in the textbook are not related to the students’ major, instead the materials are rather general and more suitable for other major. Therefore, it is needed to develop the English listening materials for the tenth grader of music performing art major. Small-Scale Research and Development (R&D) is the suitable method in developing the materials. Based on the students’ needs analysis obtained from the questionnaires which responded by 64 students and interviews which involved 4 students, the researcher found that 78.13% of the respondents assumed that the existing materials provided by the teachers are general, and further 93.75% expect a major-related English listening materials. The materials are developed by adding some musical terms, like music instruments, and topics related to musical field, like popular singer’s profile, as a step to meet the students’ needs. The experts’ validation shows that the materials are appropriate and recommended to be used. Based on the result of the study, conclusion and suggestions are directed to the English teachers in SMK Negeri 11 Medan, especially, and in other music major vocational school, generally, who are expected to provide materials which are related to the students’ major, by doing so the students might have motivation in learning English and to support their knowledge to be a professional musicians. Key words: Research and Development (R&D) method, English listening materials, Music performing art major